Enjeux littéraires, bibliques et rhétoriques dans le discours liminaire des épopées apocalyptiques renaissantes - Krawczyk, Dariusz (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The aim of this article is to analyse the prefaces to the French Renaissance apocalypticepics of the years 1576-1606 (works by Jacques de Billy, Guillaume de Chevalier,Michel Quillian and Jude Serclier) in order to understand the literary and extra-literaryissues addressed by their authors. This comparison will highlight in particular the ethos ofthe author, the problem of representation in a biblical poem and its eschatological dimension,the place of pagan fiction and encyclopaedic erudition, and the rhetorical strategiesemployed.